(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper focuses on the primacy in the operatic text of the singer’s performance. It shows how this primacy has been opposed in the whole course of opera history, making reference to the Puppet Opera in XVII-XVIII centuries; to Stanislavsky’s reforms of singers’ acting and performance; to Meyerhold’s experimentations and opera theatre directions; to the recent digital reconstruction of Maria Callas’ body in Virtual Tosca.